2005
DOI: 10.1128/aac.49.12.4980-4988.2005
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Assays Using a Luciferase-Expressing Replicon, Virus-Like Particles, and Full-Length Virus for West Nile Virus Drug Discovery

Abstract: Many flaviviruses cause significant human disease worldwide. The development of flavivirus chemotherapy requires reliable high-throughput screening (HTS) assays. Although genetic systems have been developed for many flaviviruses, their usage in antiviral HTS assays has not been well explored. Here we compare three cell-based HTS assays for West Nile virus (WNV) drug discovery: (i) an assay that uses a cell line harboring a persistently replicating subgenomic replicon (containing a deletion of viral structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
112
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 48 publications
(65 reference statements)
0
112
1
Order By: Relevance
“…2A) into cells resulted in dual-phase luciferase expression. While the first phase of luciferase expression peaked at 3 h posttransfection and declined to the background level at 10 h posttransfection, the second phase of expression started at 24 h posttransfection and increased exponentially (39). It had been demonstrated that the first phase of luciferase expression was translated from the input replicon RNA, but the second phase of luciferase expression required replicon RNA replication (39).…”
Section: Fig 4 Effects Of Isgs On Denv Infection (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…2A) into cells resulted in dual-phase luciferase expression. While the first phase of luciferase expression peaked at 3 h posttransfection and declined to the background level at 10 h posttransfection, the second phase of expression started at 24 h posttransfection and increased exponentially (39). It had been demonstrated that the first phase of luciferase expression was translated from the input replicon RNA, but the second phase of luciferase expression required replicon RNA replication (39).…”
Section: Fig 4 Effects Of Isgs On Denv Infection (A)mentioning
confidence: 99%
“…To identify ISGs that are able to inhibit WNV and/or DENV infections, we initially examined the effects of each individual ISG on WNV and DENV-1 replicon-containing virus-like particle (VLP) infections in FLP-IN T Rex-derived ISG-expressing cell lines. As described previously (39), WNV and DENV-1 VLPs were prepared by providing the viral structural proteins in trans in cells containing viral replicons. Like virions, the VLPs are able to infect permissive cells and initiate replicon RNA replication.…”
mentioning
confidence: 99%
“…Finally, toxic compounds can be scored as positive hits, and therefore must be eliminated with a counter screen measuring cellular viability. To overcome some of these hurdles, recombinant viruses or replicons have been engineered by reverse genetics to express reporter proteins, such as EGFP or luciferase, from an additional transcription unit or in frame with viral protein genes (few examples are [20][21][22][23] ). When these viruses replicate, reporter proteins are produced together with viral proteins themselves.…”
Section: Introductionmentioning
confidence: 99%
“…The WNV replicon was genetically engineered to encode a Renilla luciferase reporter and had the genes encoding for WNV structural proteins deleted. Viral structural proteins were packaged in trans to create virus-like particles as described in [10]. The WNV replicon was injected subcutaneously into the footpad of six week old B6 mice.…”
Section: Study Datamentioning
confidence: 99%